Control interno de inventarios y su incidencia en la gestión financiera de empresas comerciales - Tisalema Tisalema, María Trancito (2024)
Internal inventory control is vital to the financial management of commercial enterprises, ensuring the accuracy of accounting records and operational efficiency. An effective system encompasses policies, procedures and practices that protect assets, prevent fraud and errors, and ensure the reliability of financial information. Therefore, this research is focused on describing the various internal inventory controls and their impact on the financial management of commercial companies. A comprehensive literature review was conducted using a mixed qualitative and quantitative approach. The analysis reveals that, although international regulations such as the Committee of Sponsoring Organizations of the Treadway Commission and Control Objectives for Information and Related Technologies emphasize the importance of effective internal control and risk management, they do not specify the frequency of physical inventories, unlike other resolutions, which require physical inventories every 10 years. In addition, the adoption of advanced technologies, such as artificial intelligence, significantly improves the quality of internal control and accounting information systems, optimizing operational efficiency and regulatory compliance in various sectors. Among the conclusions is that a robust internal control system is essential to ensure the accuracy and integrity of accounting records, optimizing operational efficiency and the reliability of financial information. The integration of advanced technologies not only increases the accuracy and efficiency of accounting management, but also facilitates the detection and prevention of fraud and errors.